(untitled) - Tacon, Albert G.J. (Washington DC, 1990)
This book is a guide to the management and use of formulated feeds in semi-intensive and intensive fish and shrimp culture. Feeds represent the major variable operating costs in intensive aquaculture, and optimizing their use represents an opportunity for many farmers to increase or maintain the profitability of their enterprise. Fish farmers have an ever widening range of feed types and feeding methods from which to choose, and must carefully monitor the use of feeds in order to control costs. This book includes details of those biological, environmental, and nutritional factors which influence the feeding, growth and survival of fish and shrimp, and of which some understanding is essential in the establishment of effective feeding practices.
Keywords: Shrimps,Fish culture; Feeding